A new PAT application: Optimization of processing methods for honeysuckle flower (Lonicerae Japonicae Flos) and wild honeysuckle flower (Lonicerae Flos) - Jiangbo Hao; Zhisheng Wu; Weidong Li; Zhongshuang Zhang; Jinrui Gu (Journal of Traditional Chinese Medical Sciences, 2018)
Objective: A novel processing analytical framework of Chinese Material Medica (CMM) includes breeding process analysis, planting process analysis, producing process analysis and manufacture process analysis. In order to study this framework, we used quality control of honeysuckle flower (Lonicerae japonicae Flos) including diploid and tetraploid Lonicera japonica, and wild honeysuckle flower (Lonicerae Flos) including Lonicerae hypoglauca, Lonicerae confusa, Lonicerae fulvotomentosa and Lonicerae macranthoides as an example. Methods: A total of 360 samples were analyzed from three variables including species, growing areas, and optimization of processing methods. For quantitative analysis, chlorogenic acid (CA), isochlorogenic acid A (3, 5-DCA), and isochlorogenic acid C (4, 5-DCA) were measured with high performance liquid chromatography (HPLC). Results: The three organic acids contents are higher in wild honeysuckle flower than honeysuckle flower; L. japonica (tetraploid) is higher than L. japonica (diploid). Modern processing methods (kill-enzyme torrefaction and fixing machine drying) are popular in growing areas and are superior to traditional methods (sun and shade drying). Conclusions: Novel process analysis concepts in processing analytical technology (PAT) enriched the Chinese Material Medica contents. Keywords: Honeysuckle flower, Wild honeysuckle flower, Processing analytical technology, Quality control, Processing method